КЛИНИЧЕСКИЕ АСПЕКТЫ ТРАНСНОЗОЛОГИЧЕСКОЙ КОМОРБИДНОСТИ КЛЕЩЕВЫХ НЕЙРОИНФЕКЦИЙ (КЛЕЩЕВОЙ ЭНЦЕФАЛИТ, БОРРЕЛИОЗ) - Д. А. Этенко; О. Г. Гамов; А. В. Субботин; В. А. Семёнов (SINAPS LLC, 2013)
In article the results of clinical observations of mixed tick-borne encephalitis-Borrelia infection and mono infections of tick-borne encephalitis and borreliosis are described. The results of the comparative analysis of the severity of nervous system affection in patients with mixed infection and both variants of monoinfections are presented.